Heavy metal content of produce grown in San Juan County (New Mexico, USA). Issue 10 (14th July 2020) - Matthews, Alyce N.; Rogus, Stephanie; Jha, Gaurav; Ulery, April; Delgado, Efren; Lombard, Kevin; Hunter, Barbara; Francis, Brandon
Abstract: The Animas River Watershed has long received discharges of naturally occurring acid rock drainage; however, on August 5, 2015, three million gallons flowed into the agricultural region of Farmington, New Mexico and the Navajo Nation. Consumers and growers in the region were fearful that produce might absorb heavy metals from contaminated irrigation water originating from these rivers. Samples were collected from the region including corn ( n = 30), pumpkin ( n = 10), squash ( n = 10), and cucumber ( n = 10) then processed and tested using inductively coupled plasma-optical emission spectrometry (ICP-OES) for concentrations of nine metals of interest. These include toxic metals: Al, As, and Pb, which were compared to the World Health Organization limits, 18.29 mg d −1, 0.192 mg d −1, and 0.05 mg kg −1, respectively and essential metals: Cr, Fe, Mn, Zn, Ca, and Cu whose levels were compared to the National Academies' dietary references for tolerable upper intake levels. Results indicate that produce grown in the region contained significantly less metal than the allowable limits, except for Pb in two corn samples. This research is the first attempt to monitor and analyze heavy metal absorption of produce in the area.